Modelling of shaft based processes. Issue 2 (2nd April 2020) - Chaitanya, G. V. A.; Kamble, S.; Lollchund, R.M.; Gupta, G.S.; Chen, Z.
ABSTRACT: Shaft based processes are used in many disciplines such as in metallurgical and chemical engineering. However, their performance suffers due to the lack in understanding of solid and gas flow thus the heat and mass transfer inside the shaft. Therefore, in this article the study of solid flow has been carried out in presence of gas flow under counter-current condition. A slow moving packed bed, inside the reactor, has been considered. Particles are discharged from the bottom and gas is injected laterally. Particles have been modelled using Discrete Element Method (DEM) and gas flow has been modelled using continuum based fluid flow equations. The effect of various parameters (like particle size, gas flow rate, solid discharge rate etc., ) on the residence time of solid particles has been studied in detail. It is found that gas flow is not symmetric inside the reactor due to asymmetric distribution of voids.